Software Reliability Modeling Using Neural Network Technique - Shudhalwar, Dipak D; Agrawal, Pallavi (International Journal of Computer Sciences and Engineering, 2018)
In this paper, we propose an artificial neural network-based approach for developing the model for software reliability estimation. The use of intelligent neural network and hybrid techniques in place of the traditional statistical techniques has shown a remarkable improvement in the development of prediction models for software reliability in the recent years. Among the intelligent and the statistical techniques, it is not easy to identify the best one since their performance varies with the change in data. In this paper, firstly the neural network from the mathematical viewpoints of software reliability modeling is explained. Then it is show how to apply neural network to develop a model for the prediction of software reliability. The implementation of proposed model is done with real software failure data sets. From simulation results, the proposed model significantly outperforms the traditional software reliability models.